Dietary supplement consumption among active individuals in Saudi Arabia - Abdulrahman A. Alsayegh; Abeer S. Alzaben; Yahya M. Abu Haddash; Abdulrahman M. Busayli; Rama M. Chandika; Munirah N. Alsuhaibani; Sara A. Albishi; Mahitab A. Hanbazaza; Omar I. Abuzaid; Majed M. Alkhalaf (PLoS ONE, 2026)
Background Despite the increasing use of dietary supplements in Saudi Arabia, accurate information on their consumption patterns and predictors is essential for effective policy planning. Objective This study aimed to estimate the prevalence of dietary supplement consumption, assess perceptions regarding their health effects, and identify demographic, health-related, and knowledge- and practice-based factors influencing their use among active individuals in Saudi Arabia. Methods This cross-sectional study identified predictors of dietary supplement consumption using a Likert-scale questionnaire adapted from validated local and international tools with minor modifications. Structural equation modeling was conducted by defining multiple sets of regression equations. The analyses were performed using R software (Version 4.1.2) with the lavaan and semPlot packages. A two-tailed p-value < 0.05 was considered statistically significant. Results A total of 3,800 active individuals from 13 Saudi Arabian regions participated in this study. The prevalence of dietary supplement use among active individuals was 63.82%. Health characteristics and knowledge and practice domains showed a highly significant influence on supplement consumption, whereas the demographic domain did not show a significant association in the structural equation model, although several demographic variables were significantly associated with supplement use in bivariate analysis. Conclusion The prevalence of dietary supplement use among physically active individuals in Saudi Arabia exceeded the prevalence rates reported in several international populations, with more than three out of every five participants indicating use of dietary supplements.